1981
DOI: 10.1002/1097-0142(19810501)47:9<2162::aid-cncr2820470909>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

The seventies evolution in liver surgery for cancer

Abstract: During the past decade, one of the major changes in the field of oncology has been in the surgical approach to primary and secondary cancer of the liver. As a result of data and experience gained in liver transplantation programs and with the application of vascular surgical principles, resectability rates have been increased. The present rate of 32% has been achieved with an overall 30-day operative mortality rate of 9%. More sophisticated intraoperative and postoperative supports have been essential in achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
2

Year Published

1983
1983
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(22 citation statements)
references
References 17 publications
1
18
1
2
Order By: Relevance
“…In 8 An abundant vascular network was noted in tumor capsules, and communicating branches between blood spaces in the tumor and this vascular network were observed in all cases. Serial sections showed that tumor cells were disseminated through these communicating branches and were also present within the vascular network of the capsule in most of the resected specimens.…”
Section: Methodsmentioning
confidence: 95%
“…In 8 An abundant vascular network was noted in tumor capsules, and communicating branches between blood spaces in the tumor and this vascular network were observed in all cases. Serial sections showed that tumor cells were disseminated through these communicating branches and were also present within the vascular network of the capsule in most of the resected specimens.…”
Section: Methodsmentioning
confidence: 95%
“…Foster reviewed more than 400 hospital records of patients with metastatic liver tumor from colorectal cancer and reported in 1978 two-and five-year determinant survival, respectively, of 44% and 22%, excluding the patients who died during the initial hospitalization. 8 Fortner et al reported one-, two-, and three-year actuarial survival of 88%, 48%, and 48% excluding an operative mortality of 8%.20, 21 Wilson and Adson reported a five-year survival of 28% among 60 patients with liver metastasis from colorectal cancer, two thirds of whom were treated by wedge resection of the liver.23 Later, Adson and Van Heerden reported one-, two-, and threeyear actual survival, respectively, of 82%, 58%, and 44% among 34 patients who had major hepatic resections excluding operative deaths. 24 The authors have obtained one-, three-, and five-year actuarial survival, respectively, of 91.3%, 73%, and 52.1 % in patients with metastatic colorectal cancer without any operative mortality.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6]9 In our most recent review of 411 hepatic resections, 5 the overall operative mortality rate was 3.2 per cent. The mortality rate was the highest, 6.3 per cent (9 of 142), after trisegmentectomy and only 1.9 per cent (3 of 158) after lobectomy.…”
Section: Discussionmentioning
confidence: 98%
“…7,8,10,11 Acknowledging the limitation in comparing the survival rates without proper staging of the malignant tumor, our 1-, 3-, and 5-year actuarial survival rates of 68.5 per cent, 45.1 per cent, and 31.9 per cent, respectively, are similar to or even better than those reported in the literature. 1,4,9 The fact that more than half of our patients required trisegmentectomy to remove their massive tumors illustrates the advanced stages of malignancy in our series. Despite this, 18 patients lived more than 5 years after hepatic resection, and 14 did so after trisegmentectomy.…”
mentioning
confidence: 85%